As demandas educacionais presentes na EJA: um olhar etnográfico para o ensino de Ciências - Bär, Maira Vanessa (2020)
The Education of Young People and Adults (EJA), a type of teaching prescribed by law, has the purpose of opportunizing the completion of Basic Education to individuals who, due to various adversities, did not complete it in a time considered mandatory. Thus, every year millions of youth and adults are enrolled in the EJA program, aiming to conclude the Elementary School (Phase I; Phase II) and Secondary School, applying for jobs, Technical or Higher Education courses, among others. Given this context, this research sought to outline the profile of EJA students and their demands in science teaching, adopting the State Center for Basic Education - CEEBJA - Professor Joaquina Mattos Branco from the city of Cascavel-PR as the field of investigation. The methods selected as guidelines for the work consisted of bibliographic and documental revision for the theoretical elaboration and ethnographic method related to field research. The research was carried out in two science classes of the referred CEEBJA, one in the morning period and the other at night, during the second semester of the year 2018. The observations of the classes were written in a field diary, as well as objective/descriptive questionnaires to the students, an audiorecorded interview with the teachers and an audio-recorded dialogue with the students at the end of the school semester. These tools, allowed by the ethnographic method, configured in the elaboration of a narrative based on the theoreticians studied. Thus, initially the profile of the students who attended the classes was verified and then their interaction and participation in the classes. In addition, the methodology developed by the Science teachers in class was observed, as well as the contents made available during that process. Thus, the research showed that the profile of the classes was heterogeneous, especially the morning class, in which there were the teenage students enrolled, influencing the forwarding of those classes and the behavior of the other students. Other aspects that were verified revealed about the formation of the teachers, the methodologies used, the dynamism of the classes, the influence of learning in science in the daily life of the student and the thinking about the scientific content. Thus, it is expected that reformulations in the EJA modality will occur, especially in its compensatory and superficial format.